Enhancing the reporting of implementation research. (December 2017) - Wilson, Paul; Sales, Anne; Wensing, Michel; Aarons, Gregory; Flottorp, Signe; Glidewell, Liz; Hutchinson, Alison; Presseau, Justin; Rogers, Anne; Sevdalis, Nick; Squires, Janet; Straus, Sharon
Abstract In the 10 years since the inception ofImplementation Science, we have witnessed a continued rise in the number of submissions received, reflecting the continued global interest in methods to enhance the uptake of research findings into healthcare practice and policy. We receive over 750 submissions annually, and there is now a large gap between what is submitted and what gets published. In this editorial, we restate the journal scope and current boundaries. We also identify some specific reporting issues that if addressed will help enhance the scientific reporting quality and transparency of the manuscripts we receive. We hope that this editorial acts as a further guide to researchers seeking to publish their work inImplementation Science .